2015
DOI: 10.1080/16089677.2015.1090185
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and associations of erectile dysfunction in a South African male diabetic urban population

Abstract: Background: Erectile dysfunction (ED) is a common condition in patients with type 1 or type 2 diabetes mellitus. The prevalence and predictors in our patient population are unknown since minimal data exist for this condition in South Africa. Method: An observational, cross-sectional study was performed on 150 consecutive male patients aged ≥ 50 years, with either type 1 or type 2 diabetes mellitus, attending the Steve Biko Academic Hospital Diabetes Clinic. These patients were evaluated for diabetes mellitus c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 33 publications
4
24
0
Order By: Relevance
“…[21] The few available studies in diabetic men have shown that the sensitivity of using questionnaires is high, but that they lack specificity; also, they correlate poorly with serum testosterone, similar to the findings of the present study. [19,22,23] The Pretoria study [7] found that the ADAM questionnaire had a high sensitivity (95%) and low specificity (5%), similar to the findings of a crosssectional survey among 200 Nigerian men with T2DM. [7,24] The value of the AMS and ADAM questionnaires in SSA populations therefore remains unresolved, and they require further validation before they can be recommended in routine practice.…”
Section: Researchsupporting
confidence: 65%
See 4 more Smart Citations
“…[21] The few available studies in diabetic men have shown that the sensitivity of using questionnaires is high, but that they lack specificity; also, they correlate poorly with serum testosterone, similar to the findings of the present study. [19,22,23] The Pretoria study [7] found that the ADAM questionnaire had a high sensitivity (95%) and low specificity (5%), similar to the findings of a crosssectional survey among 200 Nigerian men with T2DM. [7,24] The value of the AMS and ADAM questionnaires in SSA populations therefore remains unresolved, and they require further validation before they can be recommended in routine practice.…”
Section: Researchsupporting
confidence: 65%
“…To date published data are available only from three countries, Nigeria, Ghana and South Africa (SA) ( Table 1). [7][8][9][10][11][12][13] These studies report a high prevalence of low serum testosterone, from 29.5% to 50%. However, only a few studies have investigated the risk factors associated with low testosterone.…”
Section: Researchmentioning
confidence: 99%
See 3 more Smart Citations